FRIENDSHIP IN A COLLECTION OF SUPERMAN IS DEAD LYRICS: FRIENDSHIP IN A COLLECTION OF SUPERMAN IS DEAD LYRICS - Mubarok, Insani Wahyu (Universitas Muhammadiyah Surabaya, 2023)
Friendship relations are one of the efforts to fulfill social-emotional needs for individuals, especially for adolescents. Simultaneously with the entry of adolescence, according to the theory of psychosocial stages. An individual is faced with the task of developing identity versus role confusion. Dumas: 2012 states that during adolescence, adolescents spend a lot of time interacting in peer groups. Superman Is Dead (abbreviated as SID) is a punk rock band from Bali, Indonesia, based at Poppies Lane II, Kuta. This music group consists of three youths from Bali, namely: vocalist Bobby Kool, bassist Eka Rock and drummer Jerinx. In the lyrics above Superman is dead conveys a message to listeners that